A New Antecedent of Career Commitment: Work to Family Positive Enhancement. (19th August 2016) - Cicek, Isık; Karaboga, Tugba; Sehitoglu, Yasin
Abstract: The importance of intellectual capital as an element of human capital motivates organizations to search the elements of work - life balance that employees consider important. For this purpose, considering career management as one of the human resources management tools, employees' commitment to their careers can be expressed as a factor that may be examined in retention. Employees committed to their career perform higher than others are not committed to their career. Therefore studying career commitment premises in work – family balance can be considered as an original subject for organizational researchers. In this research, positive synergy from work to family is studied as one of the premises of career commitment. Positive effect from work to family is studied with 2 variables: work to family enrichment and work to family positive spillover. According to findings, identity dimension of career commitment is influenced by the affect dimension and capital dimension of enrichment and by the affect dimension of positive spillover. The variance in the dimension of planning and resilience can be explained by the change in the level of spillover with negative direction.